18F-Sodium Fluoride Positron Emission Tomography Activity Predicts the Development of New Coronary Artery Calcifications. Issue 1 (January 2021) - Bellinge, Jamie W.; Francis, Roslyn J.; Lee, Sing Ching; Phillips, Michael; Rajwani, Adil; Lewis, Joshua R.; Watts, Gerald F.; Schultz, Carl J.
Abstract : Objective: The coronary calcium score (CCS) predicts cardiovascular disease risk in individuals with diabetes, and rate of progression of CCS is an additional and incremental marker of risk. 18 F-sodium fluoride positron emission tomography ( 18 F-NaF PET) detects early and active calcifications within the vasculature. We aimed to ascertain the relationship between 18 F-NaF PET activity and CCS progression in patients with diabetes. Approach and Results: We identified individuals between 50 and 80 years with diabetes and no history of clinical coronary artery disease. Those with a CCS ≥10 were invited to undergo 18 F-NaF PET scanning and then repeat CCS >2 years later. 18 F-NaF PET and CCS analysis were performed on a per-coronary and a per-patient level. We compared the proportion of CCS progressors in 18 F-NaF PET–positive versus 18 F-NaF PET–negative coronary arteries. Forty-one participants with 163 coronary arteries underwent follow-up CCS 2.8±0.5 years later. 18 F-NaF PET–positive coronary arteries (n=52) were more likely to be CCS progressors, compared with negative coronary arteries (n=111; 86.5% versus 52.3%, P <0.001). Adjusting for baseline CCS, 18 F-NaF PET–positive disease was an independent predictor of subsequent CCS progression (odds ratio, 2.92 [95% CI, 1.32–6.45], P =0.008). All subjects (100%, 15/15) with ≥2 18 F-NaF–positive coronary arteries progressed in CCS. Conclusions: In subjects with diabetes, 18 F-NaF PET positivity at baseline, independently predicted the progression of calcifications within the coronary arteries 2.8 years later. These findings suggest 18 F-NaF PET may be a promising technique for earlier identification of patients at higher risk of cardiovascular events. Abstract : Supplemental Digital Content is available in the text.